EFFECT OF CIPROFOXACIN ON GROWING CARTILAGE IN ALBINO RAT PUPS - Channa, Haji Muhammad Aslam; Ashfaq, Muhammad; Mastoi, Shah Murad; Qureshi, Muhammad Azam (Journal of Ayub Medical College Abbottabad, 2006)
Background: Administration of quinolone therapy is controversial during growing age as stated by earlier worker. The flroquinolones are currently not indicated for young children, because of arthropathy and adverse effect on growing cartilage shown by studies. However the effects of ciprofloxacin on epiphyseal growth plate has remained undocumented. This study is therefore, undertaken to determine the risk of ciprofloxacin administration an growing cartilage by prospective experimental animal study model using Wistar albino rat pups. Methods: Ciprofloxacin was administered to newly born Wistar albino rat pups with a doze of 20mg/kg body weight intraperitonealy twice a day from day-1 to day-14 after birth. The animals were sacrificed by deep ether anesthesia. The limbs were disarticulated from axial skeleton, soft tissue was removed. The intact bone mean length in millimeter of right and left humerus and femur was measured with the help of electronic vernier caliper and bones were fixed in 10% buffered farmalin. Decalcification was done in 10% nitric acid and 10% formic acid changes. After paraplast embeding, 4 mm thick longitudinal sections of the proximal long bones were cut by a rotary microtome. Routine staining with haemotoxylin and eosin was performed. Histomorphometry was done measuring the thickness of epiphyseal cartilage and was compared with similar value of control animals. The results were statistically analysed to find out the significance. Results: The ciprofloxacin induces a mordanting effect as abviated by increased basophilia. Our study reveales that cirprofloxacin administration in the newly born pups decreased the width of epiphyseal growth plate cartilage by 10.43% in humerus and 4.72% in femur as compared to the growth of control cartilage. The decrease in the width was brought about mainly by the reduced count of the proliferative cells in the proliferative zone and the diminuation in the average size of the hypertrophic condryocytes in the hypertrophic zone. The reserve zone has become markedly reduced in thickness. Conclusion: The ciprofloxacin post-natal administration effected growth plate retardation by inhibiting the mitosis in the proliferative zone and also effected the mean length of humora & femora leading to reduction in limb length of rat pups. Key words: Ciprofloxacin - Cartilage Toxicity- Cartilage growth - Bone Ossification - Growth rate - Epiphyseal plate - Chondrocyte.